Children in Iraq: the suffering and violations under the siege and the U.S. occupation - Imad Ibrahim Ali Al-Sultan; Mahmoud Khaled Al-Musafir (2011)
Many reports and research work has been shed a light about the legacy of U.S. occupation of Iraq with his allied forces ( major global , regional and local alliance) to the destruction of civilian infrastructure of social, economic, cultural and other fields in Iraq, which was reflected clearly on the rights of Iraq's political and humanitarian situation in various aspects, including the substantial negative impact on one of most important segment of Iraqi society , the children of Iraq. Therefore, this study indicates a research in documented field studies, some of which are conducted by foreign institutions such as the British research firm, published in 2007 showed that 1.2 million Iraqis were killed in the invasion and U.S. occupation in 2003, most of them children. In the time of embargo imposed by American imposed Security Council resolutions, the report of UNICEF in October 1999 mention that malnutrition as a result of the blockade caused an increase in mortality rates among children up to the highest in the world. Because of the failure of the occupation government and U.S. forces invading Iraq in the advancement of the basic responsibilities towards the children of Iraq in accordance with the provisions of the Convention on the Rights of the Child in life. Accordingly, this study will provoke the facts on the violations and suffering of the children of Iraq by U.S. forces at all levels and give proposals in order to terminate and stop the deterioration seeking the support of the international community and humanitarian organizations concerned with human rights in that respect